2011
DOI: 10.1002/adem.201100197
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Magnesium Alloys Based on MgZn and SmCo with Sensory Properties

Abstract: Reducing inertial masses of engineering equipment or vehicles to lower their energy requirements necessitates the use of lightweight materials possessing high static and cyclic strengths for lower densities. If, in doing this, over dimensioning of mechanical components is to be avoided then a design which is precisely matched to the loading leads to high elastic stresses and strains in the material employed. In order to avoid over loading and plastic deformation, the service loads applied to the component must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In contrast to the authors' previous publications [7], the results of the EDS measurements (Table 2) which were performed in order to determine the overall amounts of Co in the produced Mg alloys show good compliance to the nominal amounts of the ferromagnetic alloying element the Mg melts were inoculated with during the casting process. This can be credited to the use of the extruded powder rods, as they facilitate the alloying process and obviously increase alloying efficiency.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast to the authors' previous publications [7], the results of the EDS measurements (Table 2) which were performed in order to determine the overall amounts of Co in the produced Mg alloys show good compliance to the nominal amounts of the ferromagnetic alloying element the Mg melts were inoculated with during the casting process. This can be credited to the use of the extruded powder rods, as they facilitate the alloying process and obviously increase alloying efficiency.…”
Section: Resultsmentioning
confidence: 76%
“…The authors already demonstrated the use of Zn as an additional alloying element in low concentrations [7,8] which improves the strength and, to some degree, the castability. In order to examine the interactions of Co and standard alloying elements like Al, Zn and Mn further investigations are currently made which focus on enhancing the mechanical properties in the as-cast state and primarily the yield strength.…”
Section: Discussionmentioning
confidence: 99%